PENERAPAN PEMBELAJARAN PROCESS ORIENTED GUIDED INQUIRY LEARNING (POGIL) UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS PESERTA DIDIK - Sukma Nikmatul Karimah; Tutut Nurita (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2020)
The purpose of this research is to describe the achievements of students in improving science process skills after learning the Process Oriented Guided Inquiry Learning (POGIL) model on vibration and wave material. The research design used is the One-Group Pretest-Posttest Design with one experimental class and one replication class. The sample of this study were students of class VIII F and VIII J in one junior high school in East Java. Student pretest-posttest data were analyzed with the ¬N-Gain Score test and paired t-test. The results showed that the science process skills of students increased. Class VIII F and VIII J obtained ¬N-Gain Score of 0.8 with a high category. Paired t-test results in class VIII F and VIII J obtain a probability value of 0,000 with a decision if the probability value is less than 0.05 then there is a significant difference between pretest and posttest. Based on the results of research conducted, it can be concluded that the application of the Process Oriented Guided Inquiry Learning (POGIL) learning model on vibration and wave material can improve students' science process skills.